Question
upstudy study bank question image url

Solve the following equations for \( x \). \( \begin{array}{ll}17 .) 5^{2 x}=5^{2} & 18 \\ \text { 19. }(2.5)^{2 x+1}=(2.5)^{5} & 20 \\ \text { 21. } 10^{1-x}=100 & 22 \\ \text { 23. } 3(2.7)^{5 x}=8.1 & 24 \\ \text { 25. }\left(2^{x+1} \cdot 2^{-3}\right)^{2}=2 & 26\end{array} \)

Ask by Todd Sherman. in the United States
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

The solutions to the equations are: 1. \(x = 1\) 2. \(x = 2\) 3. \(x = -1\) 4. \(x = 0.2\) or \(x = 0.2\) 5. \(x = 2.5\)

Solution

Solve the equation \( 5^{2x}=5^{2} \). Solve the equation by following steps: - step0: Solve for \(x\): \(5^{2x}=5^{2}\) - step1: Set the exponents equal: \(2x=2\) - step2: Divide both sides: \(\frac{2x}{2}=\frac{2}{2}\) - step3: Divide the numbers: \(x=1\) Solve the equation \( (2.5)^{2x+1}=(2.5)^{5} \). Solve the equation by following steps: - step0: Solve for \(x\): \(2.5^{2x+1}=2.5^{5}\) - step1: Set the exponents equal: \(2x+1=5\) - step2: Move the constant to the right side: \(2x=5-1\) - step3: Subtract the numbers: \(2x=4\) - step4: Divide both sides: \(\frac{2x}{2}=\frac{4}{2}\) - step5: Divide the numbers: \(x=2\) Solve the equation \( 10^{1-x}=100 \). Solve the equation by following steps: - step0: Solve for \(x\): \(10^{1-x}=100\) - step1: Rewrite in exponential form: \(10^{1-x}=10^{2}\) - step2: Set the exponents equal: \(1-x=2\) - step3: Move the constant to the right side: \(-x=2-1\) - step4: Subtract the numbers: \(-x=1\) - step5: Change the signs: \(x=-1\) Solve the equation \( 3(2.7)^{5x}=8.1 \). Solve the equation by following steps: - step0: Solve for \(x\): \(3\times 2.7^{5x}=8.1\) - step1: Convert the expressions: \(3\left(\frac{27}{10}\right)^{5x}=8.1\) - step2: Multiply by the reciprocal: \(3\left(\frac{27}{10}\right)^{5x}\times \frac{1}{3}=8.1\times \frac{1}{3}\) - step3: Multiply: \(\left(\frac{27}{10}\right)^{5x}=\frac{27}{10}\) - step4: Set the exponents equal: \(5x=1\) - step5: Divide both sides: \(\frac{5x}{5}=\frac{1}{5}\) - step6: Divide the numbers: \(x=\frac{1}{5}\) Solve the equation \( \left(2^{x+1} \cdot 2^{-3}\right)^{2}=2 \). Solve the equation by following steps: - step0: Solve for \(x\): \(\left(2^{x+1}\times 2^{-3}\right)^{2}=2\) - step1: Simplify: \(2^{2\left(x-2\right)}=2\) - step2: Set the exponents equal: \(2\left(x-2\right)=1\) - step3: Divide both sides: \(\frac{2\left(x-2\right)}{2}=\frac{1}{2}\) - step4: Divide the numbers: \(x-2=\frac{1}{2}\) - step5: Move the constant to the right side: \(x=\frac{1}{2}+2\) - step6: Add the numbers: \(x=\frac{5}{2}\) The solutions to the given equations are: 1. \(5^{2x}=5^{2}\) has the solution \(x=1\). 2. \((2.5)^{2x+1}=(2.5)^{5}\) has the solution \(x=2\). 3. \(10^{1-x}=100\) has the solution \(x=-1\). 4. \(3(2.7)^{5x}=8.1\) has the solution \(x=\frac{1}{5}\) or \(x=0.2\). 5. \(\left(2^{x+1} \cdot 2^{-3}\right)^{2}=2\) has the solution \(x=\frac{5}{2}\) or \(x=2.5\).

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Extra Insights

Let's solve these equations one by one: 17. \( 5^{2x} = 5^2 \) Since the bases are the same, we can set the exponents equal to each other: \( 2x = 2 \) Dividing both sides by 2 gives us: \( x = 1 \) --- 18. \( (2.5)^{2x+1} = (2.5)^5 \) Again, since the bases are the same, we can set the exponents equal: \( 2x + 1 = 5 \) Subtracting 1 from both sides gives us: \( 2x = 4 \) Dividing by 2 results in: \( x = 2 \) --- 19. \( 10^{1-x} = 100 \) We can rewrite 100 as \( 10^2 \): \( 10^{1-x} = 10^2 \) Setting the exponents equal gives us: \( 1 - x = 2 \) Solving for \( x \): \( -x = 2 - 1 \) So, \( -x = 1 \) or \( x = -1 \). --- 20. \( 3(2.7)^{5x} = 8.1 \) First, we can divide both sides by 3: \( (2.7)^{5x} = \frac{8.1}{3} \) Calculating \( \frac{8.1}{3} \): \( (2.7)^{5x} = 2.7 \) Since the bases are the same, we can equate the exponents: \( 5x = 1 \) Dividing both sides by 5, we find: \( x = \frac{1}{5} \) --- 21. \( (2^{x+1} \cdot 2^{-3})^{2} = 2 \) Simplifying the left side, we can use exponent rules: \( 2^{(x+1) - 3} = 2^{x - 2} \) Now raising it to the power of 2: \( (2^{x - 2})^{2} = 2^{2} \) We have: \( 2^{2(x - 2)} = 2^{2} \) Equating the exponents gives us: \( 2(x - 2) = 2 \) Dividing by 2 results in: \( x - 2 = 1 \) So, \( x = 3 \). --- In summary, the solutions are: 17. \( x = 1 \) 18. \( x = 2 \) 19. \( x = -1 \) 20. \( x = \frac{1}{5} \) 21. \( x = 3 \)

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy